Kepemimpinan Transformasional Kepala Madrasah Terhadap Implementasi Kurikulum Merdeka di Probolinggo - Khalifatus Sa’adah; Ainol; Ismatul Izzah (STAI Terpadu Yogyakarta, 2023)
This research seeks to find out about the transformational leadership of madrasa principals in the implementation of the independent curriculum in institutions. This research was conducted in MAN 2 Probolinggo. This research causes a descriptive qualitative method. The object of research is the head of the madrasa and stakeholders at the MAN 2 Probolinggo madrasa. Data collection was used through observation, interviews, and documentaries. The results of his research show that: a) the transformational leadership of the madrasa head is very optimal in building morale and providing high motivation for resources in the madrasa so that readiness arises in implementing the independent curriculum, b) the implementation of the independent curriculum at MAN 2 Probolinggo has developed effectively, structured, and optimum.